2019
DOI: 10.1242/jcs.234807
|View full text |Cite
|
Sign up to set email alerts
|

Heat resilience in embryonic zebrafish revealed using an in vivo stress granule reporter

Abstract: Although the regulation of stress granules has become an intensely studied topic, current investigations of stress granule assembly, disassembly and dynamics are mainly performed in cultured cells. Here, we report the establishment of a stress granule reporter to facilitate the real-time study of stress granules in vivo. Using CRISPR/Cas9, we fused a green fluorescence protein (GFP) to endogenous G3BP1 in zebrafish. The GFP–G3BP1 reporter faithfully and robustly responded to heat stress in zebrafish embryos an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…All UV irradiated embryos used in this study continued to develop normally without observable phenotypic abnormalities up to 6 dpf, confirming the suitability of this animal model for photoactivation studies 50 . Furthermore, any small potential increase in the temperature of the embryo as a result of UV irradiation will likely be counteracted by the remarkable resilience of the zebrafish embryo (from 1dpf) to heat stress 51 .…”
Section: Resultsmentioning
confidence: 99%
“…All UV irradiated embryos used in this study continued to develop normally without observable phenotypic abnormalities up to 6 dpf, confirming the suitability of this animal model for photoactivation studies 50 . Furthermore, any small potential increase in the temperature of the embryo as a result of UV irradiation will likely be counteracted by the remarkable resilience of the zebrafish embryo (from 1dpf) to heat stress 51 .…”
Section: Resultsmentioning
confidence: 99%
“…SGs are membraneless compartments in eukaryotic cells that are dynamically induced upon varieties of stress conditions ( 12 ) and thought to be critical to maintain gene expression homeostasis during embryonic brain development ( 25 , 39 ). UBAP2L is an essential regulator for SG assembly ( 17 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of human organoids also revealed that oxygen deprivation on corticogenesis affects intermediate progenitor proliferation and underlies long-term neurodevelopmental impairment (38). SGs are membraneless compartments in eukaryotic cells that are dynamically induced upon varieties of stress conditions (12) and thought to be critical to maintain gene expression homeostasis during embryonic brain development (25,39). UBAP2L is an essential regulator for SG assembly (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…Model organisms ranging from invertebrates, such as Caenorhabditis elegans (Beam et al 2012 ) and Drosophila melanogaster (Wang et al 2004 ), to vertebrates like Xenopus laevis and the zebrafish Danio rerio have all been studied with FCS (Shi et al 2009a , b ). The zebrafish, in particular, has greatly furthered the field of developmental biology with the use of FCS and other confocal-microscopy-related quantification technologies such as FCCS, Förster resonance energy transfer (FRET) and fluorescence recovery after photobleaching (FRAP) (Deng et al 2020 ; Wang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%